Impact of balanced and unbalanced direct current bias on harmonic distortion generated by asymmetric three-phase three-leg transformers - Masoum, Mohammad Sherkat; Moses, Paul (Institution of Engineering and Technology, 2010)
The impacts of dc bias and (un)balanced operation including tank effects on harmonic distortions generated by three-phase three-leg transformers are studied. Phase imbalances in power networks can arise from unbalanced loads, imperfections in the transposition of long transmission lines and asymmetry in the structure of transformer cores. When coupled with dc biases, such as those generated by geomagnetically induced currents, the current harmonic distortion in three-phase three-leg transformers can increase significantly. A detailed theoretical study based on electromagnetic theory is performed to explain this phenomenon. A time-domain model of a non-linear three-phase three-leg transformer considering magnetic coupling and core structure asymmetry under (un)balanced dc bias is implemented. Theoretical predictions are confirmed by simulation results which are further supported by experimental tests. The main contribution of this study is a new analysis explaining the link between dc bias and (un)balanced operation on the generation of harmonic distortion in three-phase three-leg transformers.